SUBSEQUENTLY AQCUIRED ASSETS AS FIDUCIARY SECURITY ON BANK LOANS - Usanti, Trisadini Prasastinah (Jurnal Dinamika Hukum, 2016)
Collateral in terms of subsequently acquired assets namely subsequently acquired credit might be charged with fiduciary security. This collateral is not considered ideal regarding the high risk a bank must take. To minimize the risks, the bank analyzes the credit thoroughly, impose fiduciary security officials perfectly and performs monitoring of credits regularly to avoid misconduct committed by the debtor. If a default occurs, the bank will take over the assets. Nevertheless, the problems of execution on the subsequently acquired credits might arise due to debtor's default and bad debts to the third party. Consequently, subsequently acquired assets as collateral provides as additional collateral.Keywords: bank, subsequently acquired objects, fiduciary, security, loans.